Functional and nutritional replacement of gluten in gluten-free yeast-leavened breads by using β-conglycinin concentrate extracted from soybean flour. (November 2018) - Espinosa-Ramírez, Johanan; Garzon, Raquel; Serna-Saldivar, Sergio O.; Rosell, Cristina M.
Abstract: The search of proteins that could act as both structural agents and nutritional enhancers in gluten free bread is still a challenge for the food industry. The present study evaluated the inclusion of 10% β-conglycinin concentrate (βCC) extracted from defatted soybean flour to rice flour to improve the structure and protein quality of gluten-free yeast-leavened bread. βCC breadmaking performance was compared to vital gluten functionality. Batter pasting properties and bread characterization in terms of color, texture, image analysis, microstructure a, nd protein quality were assessed. βCC and gluten led to batters with higher peak viscosity and breakdown, although only βCC was able to increase the setback. The inclusion of 10% βCC in rice flour formulations led to breads with improved color parameters and protein quality. The texture properties of βCC breads did not present significant differences compared to vital gluten breads. The crumb analysis showed that βCC led to lower cell density with highest mean cell area. The micrographs showed that βCC was able to create a net-like structure similar to the one created by gluten, confirming that βCC is capable of acting as structuring agent and protein quality improver in gluten-free formulations. Graphical abstract: Image 1 Highlights: Gluten-free breads were produced with rice flour and β-conglycinin. Functionality of β-conglycinin as gluten mimetic was evaluated in rice breads. The structure and protein quality of breads was tested. β-conglycinin formed dough and bread microstructures similar to gluten. Addition of 10% β-conglycinin increased the protein quality of bread.